2012
DOI: 10.3390/ijms131216812
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformations of α-Alumina Made from Waste Aluminum via a Precipitation Technique

Abstract: We report on a recycling project in which α-Al2O3 was produced from aluminum cans because no such work has been reported in literature. Heated aluminum cans were mixed with 8.0 M of H2SO4 solution to form an Al2(SO4)3 solution. The Al2(SO4)3 salt was contained in a white semi-liquid solution with excess H2SO4; some unreacted aluminum pieces were also present. The solution was filtered and mixed with ethanol in a ratio of 2:3, to form a white solid of Al2(SO4)3·18H2O. The Al2(SO4)3·18H2O was calcined in an elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(35 citation statements)
references
References 22 publications
2
26
0
1
Order By: Relevance
“…Increasing the roasting temperature to 850°C, almost completely removes these metals, while only for Al and Cu still longer durations or higher temperatures are required. Matori et al reported that Al sulfate might survive temperatures up to 900°C without complete decomposition [53], but Cu sulfate must have completely decomposed to at least its oxysulfate form ( Table 2). This minor dissolution of Cu is due to partial solubility of its oxysulfate.…”
Section: Effect Of Roasting Temperaturementioning
confidence: 97%
“…Increasing the roasting temperature to 850°C, almost completely removes these metals, while only for Al and Cu still longer durations or higher temperatures are required. Matori et al reported that Al sulfate might survive temperatures up to 900°C without complete decomposition [53], but Cu sulfate must have completely decomposed to at least its oxysulfate form ( Table 2). This minor dissolution of Cu is due to partial solubility of its oxysulfate.…”
Section: Effect Of Roasting Temperaturementioning
confidence: 97%
“…Naskar has synthesized the alumina nanoparticles from hydrothermal process at 170 • C for 6 h using glucose and other water-based precursor materials [24]. Khamirul Amin Matori et al have reported on a recycling project in which ␣-Al 2 O 3 was produced from aluminium cans with sulphuric acid at 1200 • C [25]. Sourav Ghose et al have studied the role of tetramethyl urea on the formation of mesoporous alumina from hydrothermal method at 150 • C for 6-24 h [26].…”
Section: Introductionmentioning
confidence: 99%
“…Untuk mengetahui pengaruh dari ekses NaOH yang digunakan dalam proses hidrolisis ini, dilakukan percobaan hidrolisis kedua dengan menambah jumlah ekses NaOH dan dengan variasi pengambilan percontoh yang berbeda yaitu setiap 3 jam. (Matori et al, 2012). Persen hidrolisis pada percobaan kedua lebih rendah dibandingkan dengan percobaan pertama.…”
Section: Proses Hidrolisis Larutan Natrium Aluminatunclassified